“Words are too small”: exploring artmaking as a tool to facilitate dialogues with young South African women about their sexual and reproductive health experiences - Hartley, Felicity; Knight, Lucia; Humphries, Hilton; Trappler, Jill; Gill, Katherine; Bekker, Linda-Gail; MacKenny, Virginia; Passmore, Jo-Ann S. (Frontiers in Reproductive Health, 2023)
Background: Adolescents and young women are at high risk for sexually transmitted infections (STIs) and unintended pregnancies. However, conversations about sexual and reproductive health (S&RH) are difficult and stigmatized. Visual art-based approaches have been a useful adjunct to language-dependent interviews, encouraging embodied memory recall. Here, we explored a novel visual art-based methodology - “Stories from the Edge” - with a cohort of young women to understand how artmaking might facilitate dialogue of how S&RH experiences influenced behaviour, to enrich dialogues captured in the individual in-depth interviews (IDIs). Methods: Seven isiXhosa-speaking young women (21-25 years) were recruited into a 6-session art-based engagement, painting the stories of their S&RH experiences. Large format art making and IDIs contributed to the data set. IDIs were audio recorded, transcribed, and translated, then analyzed thematically. Results: Young women felt that the visual arts-based methodology eased barriers to communicating experiences of S&RH-seeking behaviors, with one woman commenting that “words are too small” to capture lived experiences. Artmaking provided the opportunity to express emotional complexities of the pleasures of intimate relationships, and the heartbreak of betrayal for which they had no language. Significant social relationships (family, partners, peers) influenced sexual and reproduction attitudes and practices more than healthcare facilities and staff, and more distal socio-cultural attitudes/practices. These influences shifted from adolescence to adulthood – from family to peer and partners. Conclusion: Young women valued using the art-based methodology, which facilitated recall and verbalising their S&RH experiences more fully than language-only research. The process outlined here could provide a creative method that builds communication skills to negotiate the needs and desires of young women with partners and staff at S&RH services.